Out-of-Plane Dynamic Shock Table Testing of a Mock-Up Unreinforced Stone Masonry Building (Journal of Science and Engineering, 2026)
This paper describes the results of a dynamic shock table test of an unreinforced stone masonry mock-up building. The primary objective was to study the dynamic characteristics and collapse mechanism of the walls in the out-of-plane direction. The test setup utilized a 3.6m x 6.0m shock table and a two-sided unreinforced stone masonry building mock-up with a slate roof. The walls were constructed of 0.45-m-thick, unreinforced stone masonry with mud mortar, and the roof comprised timber beams, bamboo planks and strips, mud filling, and slate shingles. The shock table test set-up uses a 2070 kg pendulum to impart dynamic shock loads to the table. The roof and walls were connected to ensure they moved together and collapsed with a single shock. The loading protocol involved seven shocks, ranging from 5 to 33 degrees of pendulum swing, and was designed to build damage gradually and culminate in full collapse. Data was collected through video recordings and six accelerometers. While the first three shocks produced minimal damage to the building despite modest accelerations, by the end of the sixth shock, both walls exhibited large vertical cracks. The last shock caused complete collapse of the building and imparted accelerations exceeding 5g to the table and 1.01g to the wall. The test results describe the dynamic characteristics of the walls, damage progression in the walls and the observed damage during a building collapse. This experiment shows that while a single horizontal shock differs from continuous ground shaking experienced in an actual earthquake the results of dynamic shock table tests are a valuable tool in understanding the seismic behaviour of unreinforced stone masonry building.